Monitoring System Using GPS for Logistic’s Key Performance Indicator - Abba Suganda Girsang; Triadi Prabowo (Advances in Science, Technology and Engineering Systems Journal, 2019)
Transportation vendors are important for distribution companies to deliver goods or products. Operational problems of logistic process in transportation vendors’ activities are difficult to track and monitor directly in the field, such as driver’s position, the delivery, and so forth. These problems result in the difficulty to measure the performance of vendors’ activities. The aim of this research is to develop a system which covers monitoring and tracking of their logistic process operation problems. The system is built based on Android integrated with GPS and GSM. This system is also equipped with the ability to recapitulate the performance of transportation vendors in running activities of logistic operation. The performance is measured from some important components in logistic process. They are task asssment, on-time delivery, completed administration and availabilty. The result of this system is capable to show the vendor transportation’s key performance indicator (KPI) and minimalize bureaucratic problems.
Keywords: Kpi; Logistic; Gps; Tracking; Transporter